Border Practices at Beitbridge Border and Johannesburg Inner City: Implications for the SADC Regional Integration Project. (May 2019) - Moyo, Inocent; Nshimbi, Christopher Changwe
Regarded not only as a line that separates South Africa and Zimbabwe to underline the interiority and exteriority of the two countries, as well as to control and manage migration and immigration, Beitbridge border effectively plays out the immigration debates and dynamics at the heart of the nation-state of South Africa. Based on a qualitative study of how migrants from other African countries are treated at this border and in Johannesburg inner city, we suggest that the harassment suffered by the migrants at the hands of border officials, including immigration officials, the police and army, is indicative of a larger dynamic that exists in the centre, which is represented by Johannesburg inner city. Such bordering and rebordering practices at the border and at the centre reflect negatively on the spirit and letter of the Southern African Development Community (SADC) regional integration project.